(untitled) (LACCEI, 2024)
Climate change is a reality in which we are all immersed, this situation generated by environmental problems, affects the rainfall that occurs in different parts of the world. These, increase on a large scale that even cause material damage in addition to human losses. Given this context, this research focuses on the collection of rainwater as a strategic means that will favor a rural district which presents intense rainfall, in addition to being one of the most affected by rains within the regions of Peru, through Said collection proposal will reduce the drainage flow that causes disasters to the population. The methodology of this study is made up of three stages. We begin with the characterization of the study area. Then, stage two is developed, which consists of hydrological modeling. Finally, the third phase consists of determining the volumes of water captured due to the runoff of precipitation on the roofs of houses, green areas and pavements. Resulting in a 3.15% decrease in the drained volume, which corresponds to the collection of reservoirs with a capacity of 400 liters/day in each house. Likewise, when the study area increases its socioeconomic level, reservoirs with a capacity of 875 liters/day can be integrated in each house, thus having a 6.89% reduction in the volume drained.